ENTREPRENEURIAL POTENTIAL STUDENTS IN ACCOUNTING CAREER COLLEGE SAN MARCOS OF PERU AND MEXICO GUADALAJARA - UNIVERSITY OF HIGH - A COMPARATIVE ANALYSIS - Gutiérrez Huby, Ana María (2011)
The present article exposes in a synthesized approach a comparative study of the students`enterpreneuring potential. The students come from the Accounting career of the San Marcos University of Peru and Guadalajara University of Mexico. The objective of the study is to show a real evidence of the entrepreneurig capacities of the alumni from both institutions. We want to make the authorities of every institution assume a firmer attitude in the management of the promotion of the development of the enterprising capacities in the student population. The present information is based on the results of a survey applied before hand to the students of the respective academic institutions. The parallel examination of both institutions has allowed an accurate approach in the knowledge of determinant variables. The alumni have been demonstrating these variables and they are related to their degree of entrepreneurig potential. The obtained results will help to propose strategic offers of action that seek to promote and to strengthen the development of the entrepreneurship spirit of the student body. We try to achieve the education of competitive individuals and that they are capable of transforming their ideas into sustainable and innovative companies.